Verdifulle ferdigheiter. Ulike perspektiv på samfunnskunnskap - Eide, Thomas Ringen (Nordidactica, 2024)
School subject skills have been increasingly actualized in the past years, believed to make subjects more useable. In social studies didactics, there are problems understanding and operationalizing skills in research, curricula, and teaching. To get a better understanding on this topic, I use Luc Boltanski og Laurent Thévenot’s theory to look at how pupils’ skills are understood and valued. I analyse perspectives in the Nordic research literature, and identify three traditions: Citizenship Education, Bildung, and Literacy, and discuss ten facets. Although skills are sparsely discussed in the literature, I find a variety of skills related to opinions about what an ideal pupil must be able to do which are heterogeneous despite commonalities. While analysing theory, in practice one can imagine that students are presented with several ideal student dispositions and choose approaches that suit them. Different perspectives have limitations and problems that are important to consider, because choice of subject facilities has academic and political implications. The article contributes to a broader understanding of subject-specific skills.